An Experimental Study on the Performance of Nano-Silica Concrete under Varying Replacement Ratios (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study presents an experimental investigation on the performance of nano-silica–modified concrete under varying cement replacement ratios. Nano-silica, owing to its high surface area and pozzolanic reactivity, was incorporated as a partial replacement of ordinary Portland cement at different percentages to evaluate its influence on concrete properties. A comprehensive experimental program was conducted to assess fresh and hardened characteristics, including workability, compressive strength, tensile strength, and durability-related parameters. The results demonstrate that the inclusion of nano-silica significantly enhances the mechanical performance and microstructural densification of concrete up to an optimum replacement level, beyond which marginal reductions in performance were observed due to particle agglomeration and reduced workability. The findings highlight the potential of nano-silica as an effective supplementary cementitious material for producing high-performance and sustainable concrete, offering improved strength and durability while reducing cement consumption.